2022
DOI: 10.1002/solr.202200573
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐Accepting PDI–Cb Interlayer for over 22% Inverted Perovskite Solar Cells with Photo‐ and Thermal Stability

Abstract: To investigate the synergistic effect of perylene diimide (PDI) unit and diphenyl‐o‐carboranyl (Cb) group, PDI–Cb with Cb groups at the bay positions of the PDI unit is synthesized. By introducing 3D carboranyl group into the bay position, PDI–Cb shows distorted geometry between PDI core and the adjacent phenyl ring of Cb due to the ring torsions, which can suppress the aggregation tendency. Furthermore, the proper lowest unoccupied molecular orbital (LUMO) energy level of −4.12 eV may be beneficial to extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Motivated by this point, substantial effort has been made regarding interface engineering at the perovskite/C 60 interface. The representative work inserts an ultrathin LiF layer between them, which demonstrates the advantage of facilitating the electron extraction by way of forming a surface dipole at the interface to reduce the interfacial nonradiative recombination loss . However, this tends to deteriorate device stability due to photothermal-accelerated Li ion diffusion during device operation. As an alternative, Liu et al have demonstrated an improved strategy using evaporated MgF x as an interlayer to simultaneously enhance the performance and stability of inverted PSC-based tandem solar cells .…”
mentioning
confidence: 99%
“…Motivated by this point, substantial effort has been made regarding interface engineering at the perovskite/C 60 interface. The representative work inserts an ultrathin LiF layer between them, which demonstrates the advantage of facilitating the electron extraction by way of forming a surface dipole at the interface to reduce the interfacial nonradiative recombination loss . However, this tends to deteriorate device stability due to photothermal-accelerated Li ion diffusion during device operation. As an alternative, Liu et al have demonstrated an improved strategy using evaporated MgF x as an interlayer to simultaneously enhance the performance and stability of inverted PSC-based tandem solar cells .…”
mentioning
confidence: 99%